To Prevent and To Educate: On the History Of Sex Education in Colombia - Tiusaba Rivas, Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2017)
During the last decade of the twentieth century, sex education in Colombia constitutes a visible fact especially in women and youth as a population causing problems to society in terms of social and economic development. Therefore, the present article aims to view, from an archeological and genealogical perspective, the prevention as a strategy in the constitution of a set of practices that seek to regulate ways of expansion and maintenance as exercises of power over life